A Comparison of Electric‐Field‐Driven and Pressure‐Driven Fiber Generation Methods for Drug Delivery. Issue 5 (31st January 2018) - Ahmed, Jubair; Matharu, Rupy Kaur; Shams, Talayeh; Illangakoon, Upulitha Eranka; Edirisinghe, Mohan
Abstract: Polymeric fibers are prepared by using electric field driven fiber production technology—electrospinning and pressure driven fiber production technology—pressurized gyration. Fibers of four different polymers: polyvinylidene fluoride (PVDF), poly(methyl methacrylate (PMMA), poly( N ‐isopropylacrylamide), and polyvinylpyridine (PVP), are spun by both techniques and differences are analyzed for their suitability as drug carriers. The diameters of electrospun fibers are larger in some cases (PVDF and PMMA), producing fibers with lower surface area. Pressurized gyration allows for a higher rate of fiber production. Additionally, drug‐loaded PVP fibers are prepared by using two poorly water‐soluble drugs (Amphotericin B and Itraconazole). In vitro dissolution studies show differences in release rate between the two types of fibers. Drug‐loaded gyrospun fibers release the drugs faster within 15 min compared to the drug‐loaded electrospun fibers. The findings suggest pressurized gyration is a promising and scalable approach to rapid fiber production for drug delivery when compared to electrospinning. Abstract : Optimized multiple polymer solutions are spun to make fibers, by both electrospinning and pressurized gyration. Electron microscopy is used to analyze morphology. Polyvinylpyridine fibers are loaded with poorly water‐soluble drugs and undergo dissolution testing. Comparisons in drug release capability of the fibers spun by the two techniques are performed. This is the first time these two vital fiber manufacturing processes are compared.